Modeling the impact of climate change for the potential distribution of the main vector and reservoirs of zoonotic cutaneous leishmaniasis due to leishmania major in Morocco - Daoudi, Mohamed; Outammassine, Abdelkrim; Olivier, David; Amane, Mounia; Beaulieu, Myriam; Akarid, Abdellatif; Ndao, Momar; Hafidi, Mohamed; Boussaa, Samia; Boumezzough, Ali (Frontiers in Tropical Diseases, 2025)
Climate change is reshaping the epidemiology of vector-borne diseases, with zoonotic cutaneous leishmaniasis (ZCL) caused by Leishmania major emerging as a growing public health concern in Morocco. This study employs ecological niche modeling (ENM) to assess the current distribution and project future impacts of climate change on L. major, its primary vector (Phlebotomus papatasi), and reservoir host (Meriones shawi) under four Representative Concentration Pathway (RCP) scenarios (2.6, 4.5, 6.0 and 8.5). Under present climate conditions, our models reveal distinct distribution patterns: L. major is concentrated in southeastern Morocco, P. papatasi is widespread across central regions, and M. shawi occupies nearly nationwide distribution except Western Sahara. Projections indicate L. major will extend its range into eastern, High Atlas, and Rif regions (1.5–1.6% habitat gain), while P. papatasi and M. shawi will expand across central and southern Morocco (3.5–5.9% gain), with minimal habitat loss (<0.6%). These findings demonstrate a possible climate-driven shift in ZCL transmission geography, with current endemic areas expanding and new risk zones emerging in previously unaffected regions. The projections underscore the urgent need for integrated surveillance and climate-adaptive control strategies to mitigate outbreaks in vulnerable regions. By linking observed distributions to future environmental shifts, this work provides a framework for proactive public health interventions in Morocco and similar endemic areas facing climate change impacts.